IMPROVING DIGITAL LITERACY OF SMA/SMK/MA STUDENTS SE CENTRAL BENGKULU DISTRICT BENGKULU PROVINCE - Octaviani, Vethy; Maryaningsih, Maryaningsih; Dinero, Rio (Jurnal Dehasen Mengabdi, 2023)
This community service activity aims to provide education so that students are wiser in using social media and the importance of access and adoption of healthy and safe internet technology, so that they can become smart citizens in the digital era and take part as smart digital citizens in the wider community and play an active role in issues important issues that are in a global context. The community service team at Dehasen University Bengkulu in collaboration with the Department of Education and Culture of Central Bengkulu Regency, Bengkulu Province and the Bengkulu Regional Police Public Relations provided counseling with material on digital literacy, namely media literacy, digital-based information retrieval, the concept of smart digital citizenship, and hoax news to SMA/SMK/MA students throughout the district. Bengkulu Tengah Bengkulu Province is located at SMAN 1 Bengkulu Tengah. This activity went well and is expected to make a positive contribution to creating intelligent and ethical individuals in the digital era.